DOES AUDIT PROBABILITY AND TAX LITERACY ON TAXPAYER COMPLIANCE? (EXPERIMENTAL STUDY OF UZBEKISTAN AND INDONESIAN STUDENT ENTREPRENEURS) - Ugli, Otabek Rakhmanov Valijon; R Nelly Nur Apandi; Arim Nasim; Inomjon Qudratov (Journal of Innovation Research and Knowledge, 2025)
Tax compliance depends on two main things: how the government manages rules and how citizens act. The study aims to address the following research problems related to audit probability and tax literacy influencing tax compliance in Uzbekistan and Indonesia. This research uses the Experiment method using the 2x2 factorial design. The experimental subjects in this study were UPI and TSUE accounting students who had done business. The research sample was 214 students. The study's results indicate that 1) the taxation audit probability influences taxpayer compliance. 2)Tax literacy influences taxpayer compliance. 3) This study cannot prove that there is a difference in the level of taxpayer compliance when two factors interact. 4)The results of this study indicate that each treatment can show differences in the level of taxpayer compliance in reporting income in their tax reports.